Butyrate inhibits Staphylococcus aureus-aggravated dermal IL-33 expression and skin inflammation through histone deacetylase inhibition - Luo, Chia-Hui; Lai, Alan Chuan-Ying; Chang, Ya-Jen (Frontiers in Immunology, 2023)
Atopic dermatitis (AD) is an inflammatory skin disease caused by the disruption of skin barrier, and is dominated by the type 2 immune responses. Patients with AD have a high risk of developing Staphylococcus aureus infection. Interleukin-33 (IL-33), an alarmin, has been implicated in the pathophysiology of AD development. Butyrate, a short chain fatty acid known to be produced from the fermentation of glycerol by the commensal skin bacterium, Staphylococcus epidermidis, has been reported to possess antimicrobial and anti-inflammatory properties that suppress inflammatory dermatoses. However, little is known about the effects of butyrate on dermal IL-33 expression and associated immune response in S. aureus-aggravated skin inflammation in the context of AD. To decipher the underlying mechanism, we established an AD-like mouse model with epidermal barrier disruption by delipidizing the dorsal skin to induce AD-like pathophysiology, followed by the epicutaneous application of S. aureus and butyrate. We discovered that S. aureus infection exacerbated IL-33 release from keratinocytes and aggravated dermal leukocyte infiltration and IL-13 expression. Moreover, we showed that butyrate could attenuate S. aureus-aggravated skin inflammation with decreased IL-33, IL-13, and leukocyte infiltration in the skin. Mechanistically, we demonstrated that butyrate suppressed IL-33 expression and ameliorated skin inflammation through histone deacetylase 3 (HDAC3) inhibition. Overall, our findings revealed the potential positive effect of butyrate in controlling inflammatory skin conditions in AD aggravated by S. aureus infection.